(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the most popular breads in the Philippines is “Pandesal,” which Filipinos regularly eat as comfort food in the morning. They frequently dip the bread in coffee or stuff it with cheese, eggs, peanut butter, and other ingredients. Many kids don’t like the flavor of bitter melon, which makes them despise the bitter vegetable. But as people age, their palates change, which is why older people like bitter melon vegetables. One of the most well-known Filipino recipes, pinakbet, uses bitter melon, or ampalaya. Even in its bitterness, its health-giving properties will remain. The results stated that using Bitter melon leaves in Pandesal to make the product achieved the expectation. There’s no significance between the assessments of the respondent as a forecited variable. Wash and dry the bitter melon leaves to reduce the bitterness itself. Respondents assessed the level of acceptability of the product in terms of taste as Satisfactory, texture, appearance, similarity, and rate as satisfactory. In this study, researchers discussed how bitter melon leaves are an ideal addition to pandesal. Since many children and adults dislike bitter melon due to its bitter taste, they frequently miss out on important nutrients like vitamins A and C and iron. In order to minimize the bitterness of bitter melon leaves without reducing the fruit’s nutritional value, researchers came up with a way to wash and dry the leaves. By soaking bitter melon leaves in the water to remove the dirt and insects and drying them using the oven or directly in the sun, without removing the nutrients in the leaves. Researchers also made certain that the dough was sweet enough before baking in order to avoid the strong bitterness of the pandesal.